The coal-formed gas theory promoting China from a gas-poor country to a major gas-producing country in the world - Chengzao JIA; Tonglou GUO; Wenhui LIU; Shengfei QIN; Shipeng HUANG; Quanyou LIU; Weilong PENG; Feng HONG; Yanling ZHANG (Petroleum Exploration and Development, 2025)
Abstract:: In the late 1970s, the theory of coal-formed gas began to take root, sprout, develop, and improve in China. After decades of development, a complete theoretical system was finally formed. The theory of coal-formed gas points out that coal measures are good gas source rocks, with gas as the main hydrocarbon generated and oil as the auxiliary. It has opened up a new exploration idea using coal-bearing humic organic matter as the gas source, transforming the theoretical guidance for natural gas exploration in China from “monism” (i.e. oil-type gas) to “dualism” (i.e. coal-formed gas and oil-type gas) and uncovering a new field of natural gas exploration. Before the establishment of the coal-formed gas theory, China was a gas-poor country with low proved gas initially-in-place (merely 2264.33×108 m3) and production (137.3×108 m3/a), corresponding to a per capita annual consumption of only 14.37 m3. Guided by the theory of coal-formed gas, the natural gas industry of China has developed rapidly. By the end of 2023, China registered the cumulative proved gas initially-in-place of 20.90×1012 m3, an annual gas production of 2 343×108 m3, and a per capita domestic gas consumption reaching 167.36 m3. The cumulative proved reserves initially-in-place and production of natural gas were dominated by coal-formed gas. Owing to this advancement, China has transformed from a gas-poor country to the fourth largest gas producer in the world. The coal-formed gas theory and the tremendous achievements made in natural gas exploration in China under its guidance have promoted China from a gas-poor country to a major gas-producing country in the world.